4-Chloro-N-(pyrazin-2-yl)aniline - Wan Saffiee, Wan Ainna Mardhiah (International Union of Crystallography, 2008)
In the title compound, C(10)H(8)ClN(3), the dihedral angle between the aromatic rings is 43.0 (1)° and the bridging C—N—C angle is 128.19 (16)°. The amino N atom of one molecule forms a hydrogen bond to the 1-N atom of an adjacent pyrazinyl ring, generating an inversion dimer.